Effect of repetition collection of semen on its characters of two types of local cock in Syria (Latakia University Journal -Biological Sciences Series, 2020)
This Study was carried out at the Center of Animal production ( Fedio), Faculty of Agriculture, in order to evaluate the effect of repetition collection on some semen characteristics of Brown, Black and White types of local roster in syria, Where semen was collected daily, twice and three times a week. The results showed no difference(p0.05) between the number of times of collection in the Brown type and Black and White type. The average value of total movement in  the Brown type was 93.31, 95.1, and 93.22%  using daily collection, twice a week and three times a week respectively whereas it was 88.12, 90.02 and 87.14% respectively in White and black type. Additionally, the average concentration was 5.82, 5.91 and 5.93 million sperm/ ml respectively in the Brown type, and 3.21, 3.33 and 3.34 million sperm/ml respectively in white and black. Finally, our results showed that There were no significant differences between the mean percentage of dead sperm between the both studied types; that attained  6.69 , 4.88 and 6.78% respectively in the Brown and 11.88, 9.98, and 12.86% respectively in the Black and White. أجري هذا البحث في مركز بحوث الإنتاج الحيواني بفيديو، التابع لكلية الزراعة في جامعة تشرين ومخابر الكلية بهدف دراسة تأثير تكرار جمع السائل المنوي على بعض خصائصه عند نمطين من الديك المحلي في سوريا (بني اللون، أبيض وأسود اللون)، حيث تم جمع السائل المنوي يومياً، مرتين أسبوعياً، وثلاث مرات أسبوعياً. أظهرت النتائج تماثل لون السائل المنوي فهو أبيض لؤلؤي عند النمطين المدروسين، في حين تبين وجود فروق معنوية 0.05) >P ) بين النمطين الظاهرين المدروسين للريش في جميع المؤشرات المدروسة الأخرى (الحجم، الحركة الإجمالية، التركيز، انخفاض نسبة الحيوانات المنوية الميتة). كما أظهرت النتائج تفوق معنوي عند جمع السائل المنوي مرتين بالأسبوع للنمط بني اللون على النمط أبيض وأسود اللون من حيث متوسط حجم القذفة،  إذ بلغ حوالي 0.7 و 0.5 مل على التوالي بالمقارنة مع الجمع يومياً والذي بلغ حوالي 0.3  و 0.1 مل على التوالي   والجمع ثلاث مرات بالأسبوع حيث بلغ حوالي  0.33 و 0.12 مل على التوالي، في حين لا يوجد أي فروق معنوية(0.05